Manufacturing enterprises' gross margins and performance: A study on the moderating effect of management expenses and R&D expenses - ZHANG, Jiuliu (Institutional Knowledge at Singapore Management University, 2024)
In the context of globalization, manufacturing enterprises are integral to national economies, with their financial stability closely related to increasingly fierce market competition. Among various financial metrics, gross margin stands out as a key indicator of product profitability, significantly impacting production decisions, cost control, and pricing strategies. Understanding the relationship between the gross margins of manufacturing enterprises and their performance is essential for optimizing their financial structures and enhancing their market competitiveness. The study aims to investigate the correlation between gross margin and enterprise performance by developing complex, scientifically sound models and utilizing big data analysis technology. Additionally, it examines how management and R&D expenses may potentially moderate this relationship, offering both theoretical foundations and practical guidance for enterprises' financial decision-making. The study formulates Hypothesis 1 (H1), which proposes a linear relationship between manufacturing enterprises' gross margins and performance. Hypothesis 2 (H2) suggests that management and R&D expenses serve as moderators of this relationship. Lastly, Hypothesis 3 (H3) posits that variations in the relationship between gross margin and performance can be observed across different industries due to industry characteristics. The research design targets Chinese listed manufacturing enterprises, employing databases such as CNKI and Wind to conduct empirical analyses based on annual reports of these enterprises. Enterprise performance is evaluated using return on equity (ROE) and earnings per share (EPS), while control variables—such as enterprise size (Size), age (Age), and asset-liability ratio (Leverage)—are included to mitigate the influence of other factors. Seven models are developed to assess the effects of gross margin, management expenses, and R&D expenses on innovation performance, growth performance, and overall enterprise performance, as well as the interactions among these factors. Models 1 to 4 focus on the direct impacts of gross margin, management expenses, and R&D expenses on innovation and growth performance, as well as the moderating effects of management and R&D expenses, respectively. Model 5 illustrates that external environmental factors not only have a direct impact on enterprise performance but also mediate the impact of gross margin on enterprise performance through interactions with gross margin. It also considers the complex effects of enterprise size, age, and leverage. Model 6 highlights the impact of industry characteristics on performance outcomes, demonstrating the moderating effect of industry characteristics via interactions among gross margin, R&D expenses, and industry type. It incorporates year fixed effects to take time factors into account. Model 7 explores non-linear interactions among gross margin, R&D expenses, and management expenses, using quadratic interaction terms to assess changes in marginal effects in complex relationships. Empirical findings reveal a significant positive correlation between gross margin and enterprise performance, thereby validating H1 and underscoring the importance of robust profitability for sustainable enterprise growth. The moderating effects of management and R&D expenses offer new perspectives for cost control strategies. Specifically, enterprises with lower management expenses show a stronger positive correlation between gross margin and enterprise performance, highlighting the importance of cost management. R&D expenses also moderate this correlation, emphasizing the long-term necessity of sustained investment in enterprise development. The study contributes valuable insights into the financial management and strategic positioning of manufacturing enterprises at both theoretical and practical levels. It underscores the importance of enhancing gross margin while thoughtfully planning management and R&D expenses to bolster core competitiveness and market stability in a globalized market environment. The limitations of the study include its focus on listed companies; future research could expand to include small and medium-sized enterprises (SMEs) to enhance the generalizability of the findings. Additionally, incorporating macroeconomic factors and the global trade landscape could further enrich the assessment of the dynamic relationship between gross margin and enterprise performance.